2021
DOI: 10.1088/1742-6596/1720/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking Lesson in Improving Digital Literacy for Rural Area Children via CS Unplugged

Abstract: The advantage of computational tools over human brains is the speed, but the initiative ability of human brains is not owned by computational tools. The perfect combination of thinking and computing lays the foundation of science and gives birth to a series of achievements in technology. The introduction of technology through the subjects of Information and Communication Technology (ICT) in schools nowadays is just limited to using the applications. Computational thinking gives knowledge that builds structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
0
10
0
5
Order By: Relevance
“…La muestra del grupo rural (N=8) es poco numerosa, por lo que los datos obtenidos deben ser contrastados con estudios más amplios. En esta línea, Yuliana et al (2021) muestran una mejora del Pensamiento Computacional en estudiantes rurales tras realizar formación desenchufada.…”
Section: Discussionunclassified
“…La muestra del grupo rural (N=8) es poco numerosa, por lo que los datos obtenidos deben ser contrastados con estudios más amplios. En esta línea, Yuliana et al (2021) muestran una mejora del Pensamiento Computacional en estudiantes rurales tras realizar formación desenchufada.…”
Section: Discussionunclassified
“…Pengertian alat digital atau gadget juga perlu diperkenalkan dengan anak. Alat digital merupakan sarana komunikasi yang digunakan pada saat ini, alat digital juga menjadi alat yang digunakan manusia untuk melaksanakan kegiatan lebih produktif, jika digunakan dengan sesuai porsinya (Yuliana et al, 2021).…”
Section: Pembahasanunclassified
“…Wohl's study, for example, demonstrates that the unplugged computer science teaching method may effectively impart rather complicated topics (such as computational thinking) (Wohl et al, 2015). Recent research by Yuliana and Saxena also indicates that CSU courses may help young children dramatically enhance their level of Computational Thinking (Saxena et al, 2020;Yuliana I et al, 2021). Chinese researchers have recently conducted various CSU courses to explore the enhancement of students' Computational Thinking Sun, L. et al, 2021).…”
Section: Impact Of Ct Levelsmentioning
confidence: 99%
“…Brackmann demonstrated a study of CSU courses conducted in disadvantaged parts of Brazil, which revealed that the unplugged technique may significantly increase students' problem-solving abilities in these impoverished settings (Brackmann et al, 2019). In addition, many researchers from different countries have also paid attention to the effect of unplugged computer science curriculum on children, and their research has achieved similar positive results (Conde et al, 2017;DELAL & ONER, 2020;Hsu & Liang, 2021;Lee & Junoh, 2019;Saxena et al, 2020;Sysło & Kwiatkowska, 2014;Un-Jou K et al, 2020;Wohl et al, 2015;Yuliana I et al, 2021).…”
Section: Introductionmentioning
confidence: 97%